2018
DOI: 10.3354/dao03240
|View full text |Cite
|
Sign up to set email alerts
|

Oomycete parasites in freshwater copepods of Patagonia: effects on survival and recruitment

Abstract: Copepods are hosts to various oomycete parasite species, but the effects of pathogens on copepod populations have rarely been studied. This study aimed to characterize oomycete infection in the freshwater copepod Parabroteas sarsi in a temporary pond in Patagonia (Argentina). A complete hydroperiod was monitored, evaluating environmental variables as influencing factors in the oomycete infections. Laboratory experiments were performed to evaluate the susceptibility of infected copepods to consumption by predat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 55 publications
2
11
0
2
Order By: Relevance
“…Since we did not quantify the number of eggs per egg sack, only the number of hatched nauplii, we are unsure whether this effect was a result of increased number of eggs per egg sack from Saprolegnia ‐exposed mothers or of lower egg mortality rates. The increased fecundity of Saprolegnia ‐exposed females is especially surprising since all previously described oomycetes infecting freshwater copepods are brood parasites that destroy egg sacks and reduce reproductive output (Redfield and Vincent 1979; Burns 1989; Miao and Nauwerck 1999; Valois and Burns 2016; Garcia et al 2018). One possible explanation for the increased reproductive output of Saprolegnia ‐exposed E. baikalensis individuals is compensation by infected mothers for their infection‐associated shorter life span, an idea known as the “terminal investment hypothesis” or “fecundity compensation” (Minchella and Loverde 1981; Velando et al 2006; Vale and Little 2012; Brannelly et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we did not quantify the number of eggs per egg sack, only the number of hatched nauplii, we are unsure whether this effect was a result of increased number of eggs per egg sack from Saprolegnia ‐exposed mothers or of lower egg mortality rates. The increased fecundity of Saprolegnia ‐exposed females is especially surprising since all previously described oomycetes infecting freshwater copepods are brood parasites that destroy egg sacks and reduce reproductive output (Redfield and Vincent 1979; Burns 1989; Miao and Nauwerck 1999; Valois and Burns 2016; Garcia et al 2018). One possible explanation for the increased reproductive output of Saprolegnia ‐exposed E. baikalensis individuals is compensation by infected mothers for their infection‐associated shorter life span, an idea known as the “terminal investment hypothesis” or “fecundity compensation” (Minchella and Loverde 1981; Velando et al 2006; Vale and Little 2012; Brannelly et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Warming temperatures may also affect copepods such as E. baikalensis through increasing impact of parasites at higher temperatures (e.g., Miao and Nauwerck 1999; Garcia et al 2018). As early as 1926, Lake Baikal researchers documented occasional mass epizootics of a fungal parasite, putatively identified as Saprolegnia sp.…”
mentioning
confidence: 99%
“…in freshwater copepods. Garcia et al (2018) through laboratory experiments have shown that oomycetes are not lethal to females in the short-term and do not affect their susceptibility to insect predation. However, the proportion of females decreased after the spread of the infection, when the daily water temperature increased above 20 °C.…”
mentioning
confidence: 99%
“…High temperatures can accelerate metabolism and oxygen consumption, leading to excessive use of protein and a low survival rate (Li et al, 2009;Garcia & Diéguez, 2014). It is possible that a combination of these factors imposes severe restraints on P. sarsi females from spring onwards, differentially affecting their survival (Garcia et al, 2018). However, little is known regarding this aspect and further investigation is required on the subject.…”
mentioning
confidence: 99%
See 1 more Smart Citation